Comparison of Hemoglobin Alc, Glycated Albumin and Fasting Plasma Glucose for Prediction of Arterial Stiffness in Chinese Adults - Wen J (Dove Medical Press, 2020)
Jianghua Wen, 1,* Fang Hu, 2,* Qiong Yang 3 1Department of Health Examination, Jiangmen Central Hospital, Jiangmen 529070, Guangdong, People’s Republic of China; 2Department of Endocrinology, The Fifth Affiliated Hospital, Sun Yat-sen University, Zhuhai 519000, Guangdong, People’s Republic of China; 3Department of Endocrinology, Guilin Medical University Affiliated Hospital, Guilin 541001, Guangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiong YangDepartment of Endocrinology, Guilin Medical University Affiliated Hospital, Guilin 541001, Guangxi, People’s Republic of ChinaTel +8613635189559Fax +8607732823984Email 63269961@qq.comObjective: Although diabetes is closely related to cardiovascular disease, there are some disputes whether diabetes can promote arterial stiffness. Therefore, the objective of this study is to compare the predictive abilities of related-glycemic markers including fast plasma glucose (FPG), glycated hemoglobin (HbAlc) and glycated albumin (GA) for the arterial stiffness.Methods: In the present study, 3640 subjects (2171 men, 1469 women) were enrolled, and anthropometrics, brachial ankle pulse wave velocity (baPWV) and other laboratory data were obtained. Spearman correlation and multivariate logistic regression analyses were used to evaluate the relationships between FPG, HbAlc, GA and baPWV.Results: Age, BMI, blood pressure, blood lipids, γ-Glutamyl transpeptidase, uric acid, hypersensitive C-reactive protein, baPWV, FPG, HbAlc, GA, estimated glomerular filtration rate and the incidences of diabetes and hypertension in high baPWV group were much greater than those in control group. Moreover, these above three glycemic markers were positively related to baPWV, and the correlation coefficient of HbAlc was the highest. After adjusting the above factors, HbAlc and FPG, but not GA, were still positively associated with baPWV regardless of diabetes status.Conclusion: Our data demonstrated that, regardless of diabetes status, HbAlc and FPG were superior to GA for predicting arterial stiffness and HbAlc had the highest correlation with arterial stiffness, revealing that HbAlc may be regarded as an early diagnosis marker for atherosclerosis.Keywords: diabetes, glycemic markers, cardiovascular disease, brachial ankle pulse wave velocity